2018
DOI: 10.22159/ijpps.2018v10i2.23452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Common Carp and African Catfish Oils on Rats Fed on High-Fat Diet

Abstract: Objective: The present study was designed to study the effect of common carp and African catfish oils on the lipid profiles and liver functions in rats fed on high-fat diets, also fatty acids were assessed in both oils by gas-liquid chromatography (GLC). Methods:A biological experiment on rats was designed to raise fat in the diet and to study the effect of treatment with common carp and African catfish oils for 6 w (by the stomach tube) and then evaluate their impact on blood lipid profile and liver functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In modern century, people prefer to a sedentary lifestyle and a lack of exercise which are associated with increased prevalence of diabetes mellitus, obesity, hypertension, and hypertriglyceridemia. These are considered to be important causes of NAFLD and its more destructive form, i.e., non-alcoholic steatohepatitis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In modern century, people prefer to a sedentary lifestyle and a lack of exercise which are associated with increased prevalence of diabetes mellitus, obesity, hypertension, and hypertriglyceridemia. These are considered to be important causes of NAFLD and its more destructive form, i.e., non-alcoholic steatohepatitis [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in the secretion of hepatic enzymes from injured hepatocytes into blood circulation is commonly observed in a hepatic disorder like NAFLD, which is commonly associated with obesity [31]. Moreover, many recent studies have shown that fatty liver is associated with cardiovascular disease, kidney disease, colon cancer, and osteoporosis [32]. Further, the rise in serum CRP level in low calcium diet confirms the hepatic injury as a result of oxidative stress.…”
Section: Das and Choudhurimentioning
confidence: 98%
“…As fatty acids possess numerous health benefits [1][2][3][4][5][6][7][8][9] they are recognized as essential nutrients in both human and animal diets. Fatty acids are also used in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%